A method for detecting the atmospheric refraction effect using satellite remote sensing. Issue 10 (2nd October 2016) - Li, Shaoning; Zhang, Guo; Tang, Xinming; Huang, Wenchao
ABSTRACT: The atmospheric refraction effect seriously restricts the precision of satellite measurements. Various atmospheric refraction models have been proposed to solve the bending effect due to refraction. But the atmosphere shows a complicated spatio-temporal distribution due to turbulences, which affects the precision of the atmosphere models. In this study, we proposed a novel method to detect the atmospheric refraction effect according to the dispersion of the electromagnetic wave. Depending on one satellite image only, we can invert the displacement of atmospheric refraction effect. And this method makes it a reality without constructing the atmosphere model and monitoring a series of meteorological data. In the experiment, two high-resolution images were used to validate the method, an inclined shooting scene at zenith angle of 30° and a vertical shooting scene as a control. The result is close to the value calculated by the atmospheric refraction model. So the proposed method is effective to detect the atmospheric refraction effect using satellite remote sensing.